High incidence of bites and stings by snakes and other animals among rubber tappers and Amazonian Indians of the Jurua Valley, Acre State, Brazil. - Pierini, S; Warrell, D; de Paulo, A; Theakston, R (1996)
Among forest-dwelling Amazonian Indians and rubber tappers (seringueiros) of the Juruá valley in Acre State, north-western Brazil, snakebite is an important cause of morbidity and death. Overall, 13% of a surveyed population had been bitten during their lifetime. Seventeen per cent of Katukina Indians, but only 8% of Ashaninkas, had been bitten by snakes reflecting, perhaps, different levels of traditional knowledge of the forest and its dangers. Most bites occurred in the jungle or on jungle trails (56%), while people were working (41%) or walking (26%), and were inflicted on the feet (54%). Ninety per cent of bite victims received treatment, usually traditional (93%); the majority (80%) recovered fully. Mortality was estimated at about 400 deaths per 100,000 population per lifetime. Bites and stings from other venomous forest and river animals, especially the freshwater sting ray (Potamotrygon sp.), were also extremely common. One death from an ant bite was recorded.